INNOVATIVE DESIGN AND FABRICATION OF FIXTURES FOR ENHANCED ULTRASONIC TESTING - Hakim, Rahman; Hapsari, Windi; Irawan, Benndy Haddli (Jurnal Rekayasa Mesin, 2025)
Ultrasonic Non-Destructive Testing (UT) is essential in manufacturing to ensure measurement accuracy by calibrating tools against specified standards. However, UT calibration often faces challenges such as oil spills, usability issues, and lengthy processes. This study addresses these challenges by designing a specialized fixture to streamline the calibration of a 33.8 kg cylindrical UT calibration block. The fixture's design focuses on user requirements, enabling smooth block rotation and effective oil management during calibration. Key design principles were applied, including Degrees of Freedom (DoF) and locating and clamping mechanisms. Finite Element Method (FEM) simulations demonstrated a maximum stress value of 18.495 MPa and a Factor of Safety (FoS) of 22.89, confirming the fixture’s structural reliability. The proposed fixture reduced calibration cycle time by 48.7%, significantly enhancing efficiency. In conclusion, the fixture offers a safe, practical, and effective solution to optimize UT equipment calibration.